An Analysis of Competitive Strategies from Organizations in the Water and Sanitation Sector - Melo, Flávio José de (2017)
Competitive strategies are considered as one of the central elements for all management systems. The purpose of this study was to analyze the main strategic policies and prerogatives based on competitive advantages. Regarding the methodological approach, this study can beclassified as a documentaryand qualitative research. The sample for this research comprised five companies listed on the BM&F Bovespa market inthe water and sanitation economic subsector. The analysis of this study was carried out through content analysis and correspondence analysis techniques (ANACOR). Data processing and statistical inferencing of the reports   were made with the aid of Atlas.ti, Statistical Package for the Social Sciences (SPSS 20) and Wordle net software. The tests carried out using content analysis and correspondence analysis led to the conclusion that most companies mainly focus their actions on partnership strategies. It could also beconcluded that the main strategies that have a direct impact on management are: programs aimed at reducing costs through technological efficiency, resource optimization, operational improvements and socio-environmental management.